The Influence of Locally Generated Revenue, Public Allocation Funds and Specific To Financial Performance of The Region in The City/Regency Government in Aceh Province - Putra, Zainal (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The purpose of this research are: (1). To know how the condition of region ownsource revenue, the general allocation fund, special allocation fund and regionalfinancial performance , (2). To find out the influence of region own sourcerevenue, the general allocation fund, special allocation fund to the region financialperformance, (3). To know the influence of region own source revenue to theregion financial performance, (4). To find out the influence of the generalallocation fund to the region financial performance, (5). to know the effect of thespecial allocation fund toward region financial performance. The data used in thisresearch is a secondary data obtained from the office of BPK RI Aceh provinceRepresentative. The data collected in the form of pooling data in period of 2008-2012. The entire population in this research are sampled as many as 23 regencies/ cities in Aceh province. In analyzing the data using multiple linear regressionmodels. The results showed that: (1). Regencies / cities in Aceh province thecategory of of region finance ability is “very less